Enriching English vocabulary of young learners by using the “Word Guess” game and flashcard media - Utami, Irma Fajar Tri; Lestari, Titis Yekti; Rosyta, Merie Dreana Kamelia; Indriani, Lilia (Journal of English Language Teaching and Learning (JETLE), 2024)
This research aims to introduce English to young learners by enriching their vocabulary through the "Word Guess" game with flashcard media. The study used the Classroom Action Research method, involving planning, action, observation, and reflection cycles. The participants were 30 class B children from a private kindergarten in Magelang Regency, comprising 17 boys and 13 girls. The test results revealed that using the "Word Guess" game and flashcard media significantly improved the children’s English vocabulary and learning motivation. Students’ comprehension achievements reached 80%, while their learning motivation increased by 83.33%. Furthermore, the implementation of this method led to a 40% improvement in students’ knowledge, demonstrating the effectiveness of combining the "Word Guess" game with flashcards. The "Word Guess" game, enhanced by the use of colorful flashcards, made learning English enjoyable and interactive for the young learners. The activities encouraged active participation, improved focus, and helped build a positive attitude toward learning English. In conclusion, the findings indicate that the "Word Guess" game using flashcard media is an effective and engaging strategy for enriching English vocabulary among young learners. It not only boosts comprehension and motivation but also supports the development of foundational language skills.